1995
DOI: 10.1074/jbc.270.15.8506
|View full text |Cite
|
Sign up to set email alerts
|

The Protooncogene c- jun Contains an Unusual Estrogen-inducible Enhancer within the Coding Sequence

Abstract: Estrogens have previously been shown to induce c-jun mRNA levels in target cells during hormone induced proliferation, and this appears to be a primary hormonal response involving transcriptional activation. In this report we have now identified an estrogen dependent enhancer within the coding sequence of c-jun. This element has the sequence GCAGAnnnTGACC which is identical to the consensus estrogen response element GGTCAnnnTGACC in the second half site, but varies considerably in the first half site. Syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 50 publications
1
43
0
Order By: Relevance
“…These included the fos, myc, and jun genes previously known to be stimulated by estrogen (15,26,27), which thereby validate our results. Here we extend the findings and implicate PI3K action in protooncogene up-regulation by E 2 .…”
Section: Resultssupporting
confidence: 76%
“…These included the fos, myc, and jun genes previously known to be stimulated by estrogen (15,26,27), which thereby validate our results. Here we extend the findings and implicate PI3K action in protooncogene up-regulation by E 2 .…”
Section: Resultssupporting
confidence: 76%
“…Screening of the cyclin D1 promoter revealed that it lacks an estrogenresponse element (ERE), but contains an AP-1-binding site sequence located at À953 to À947 (Motokura and Arnold, 1993). Promoters of Jun and Fos are known to have functional EREs (Weisz and Rosales, 1990;Hyder et al, 1995), and expressions of c-Jun and c-Fos have reportedly been induced by estrogen in animal models (Webb et al, 1993). Our immunohistochemical analysis in human endometrial tissues revealed that expressions of c-Jun in the glandular cells was observed only in the proliferative phase (Figures 1c and d), but c-Fos expression was observed in both the proliferative and secretory phases.…”
Section: Serial Upregulation Of Cyclins and Cdks Under Treatment Withmentioning
confidence: 81%
“…Although this system has been reported to achieve a 100-fold induction of gene expression in vitro, a disadvantage of using estrogen-based systems is that endogenous genes containing sequence elements similar to the consensus estrogen response element may also be modulated in response to estrogen treatment. For example the c-jun promoter contains such a sequence, suggesting a transcriptional mechanism for the increased c-jun mRNA levels found in cells during hormone-induced proliferation (Hyder et al 1995). Other endogenous genes have also been reported to contain estrogen-regulated sequences (Hyder et al 2000).…”
Section: Estrogen-based Inducible Systemsmentioning
confidence: 99%